Snapdragons: melting snow - Strachan, Linda; Adams, Arlene (Oxford University Press UK, 2004)
Everyone joins in building a big snowman, but when the sun comes out the snowman starts to melt. The children feel sad, but Mum cheers them up wby making some snowmen ice-lollies